Bybelse inspirasie in die poësie van ’n Hugenoot: A. D ’A ubigné - Plessis, M. J. H. du (Koers, 1981)
The origin of the “Tragiques” of Agrippa d'Auhigni is to be sought in the poet's personal involvement in the religious struggle of the late sixteenth century in France. He experiences as a sense of vocation the need to give poetic expression to the struggle as seen from the Huguenot point of view. The “Tragiques”, an epic in seven books, portrays not only the historical events, but is also polemical and satirical in nature, where the Catholic Church is represented as the enemy of the nation, the handmaiden of Satan. 7 his reformatory epic therefore has as historical basis the religious wars which hare to be interpreted analogically with the experiences of the nation of Israel in the Old Testament. It is an application and interpretation of biblical events in terms of contemporary events. The central theme is the reformatory concept of "... go away, leave Babylon'’ (Luther), added to the promise of a promised land (the promise to A braham in Genesis 15). The Huguenot becomes the elect, the one who has to bring the message oj salvation, and he is the one who has been granted mercy as the bearer of the Scriptures as the only Way to Christ. In this message the author is like the biblical prophet who has to translate the word into action, and the poetry springs from his own experience in the midst of the struggle.